Polishing of treated palm oil mill effluent (POME) from ponding system by electrocoagulation process - Bashir, M.J.K. (IWA Publishing, 2016)
As the ponding system used to treat palm oil mill effluent (POME) frequently fails to satisfy the discharge standard in Malaysia, the present study aimed to resolve this problem using an optimized electrocoagulation process. Thus, a central composite design (CCD) module in response surface methodology was employed to optimize the interactions of process variables, namely current density, contact time and initial pH targeted on maximum removal of chemical oxygen demand (COD), colour and turbidity with satisfactory pH of discharge POME. The batch study was initially designed by CCD and statistical models of responses were subsequently derived to indicate the significant terms of interactive process variables. All models were verified by analysis of variance showing model significances with Prob >F< 0.01. The optimum performance was obtained at the current density of 56 mA/cm2, contact time of 65 min and initial pH of 4.5, rendering complete removal of colour and turbidity with COD removal of 75.4. The pH of post-treated POME of 7.6 was achieved, which is suitable for direct discharge. These predicted outputs were subsequently confirmed by insignificant standard deviation readings between predicted and actual values. This optimum condition also permitted the simultaneous removal of NH3-N, and various metal ions, signifying the superiority of the electrocoagulation process optimized by CCD. Â© IWA Publishing 2016.